Identificación y Recuperación de Valores Ancestrales Afrocolombianos en la Región Pacífico - Olaya Garcerá, Jorge Eliécer (Universidad Santiago de Cali, 2020)
Based on the roots and convictions of the researchers - the rhizomatic study ventured into the identification and recovery of Afro-Colombian ancestral values in the Pacific Region (Colombia), generating two sequential and complementary stages for this purpose: language contact with elders and older adults from two Ancestral Black Communities Councils in Buenaventura and in La Playa respectively (Valle-Colombia), and the subsequent pedagogical mediation with young people from the Ancestral Black Communities Council of La Bocana (Valle-Colombia). From a rhizomatic methodological structure based on the positions of Deleuze andGuattari (2005), the respective interactions were conducted in a holistically way, under the recovery of human networks and language, in addition to dynamics such as the cane handover, all of the former with strong roots in the praxis of Afro-Colombian communities in general. The obtained results led to significant findings both at the axiological level, and in the terms of emerging cultural elements, in its final phase the research allowed to assertively show the realization of padagogical mediations achieving to reaffirm and recover the Afro-Colombian ancestral values in the context of their new generations.